GAMBARAN KEMANDIRIAN DAN COPING STRESS SISWA SMA/SMK YANG MENJALANI PEMBELAJARAN DARING - Hyoscyamina, Darosy Endah; Suparno, Suparno; Karim, Chamilul Hikam Al; Abidin, Zaenal (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2023)
The aim of this research is to find out a picture of student independence and find out the stress coping strategies used by students in online learning during the Covid-19 pandemic.The research method used is a qualitative approach. Data collection methods were carried out using in-depth interviews directly or using online media such as the Zoom application and by telephone. The participants in this research were 10 high school/vocational school students who had carried out online learning for at least 6 months and lived with their parents. Informed consent was provided via the google form link.The results of the research show that based on data analysis it is known that there are five themes on independence and five themes on stress coping strategies. Responsibility, initiative, independence, having good self-control and being able to make decisions are the themes that emerge in the picture of student independence. The five themes that emerged in the stress coping strategy were religious coping, ability to assess situations, self-confidence, adaptability and ability to relax.